Uji Parameter Spesifik dan Non Spesifik p ada Kopi Robusta ( Coffea canephora ) - Azmi Prasasti; Stephanie Devi Artemesia; Firda Ihza Firgilia; Wulan Dari Nur Wahyu Liana (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Robusta coffee is the most widely cultivated type of coffee in Indonesia. Caffeine in coffee determines the taste and aroma of coffee. Extract standardization determines the quality of the extract. Therefore, this study aims to standardize the extract including organoleptic extract, calculating the yield weight, moisture content and ash content, as well as testing the caffeine content of Robusta coffee using the gravimetic method. The solvent used was ethyl acetate 99% with refluks extraction method. The results showed that the yield weight was 9,712%, the moisture content was 4,83% and the as content was 0,43%. The water content and ash content values meet the standards set by Farmakope Herbal Indonesia. Meanwhile, the value of caffeine levels shows 7,91 ± 0,01 %